A bibliometric analysis of the study of urban green spaces and health behaviors - Zhang, Sining; Li, Xiaopeng; Chen, Zhanglei; Ouyang, Yu (Frontiers in Public Health, 2022)
Urban green space can supply a range of ecosystem services and general health benefits for people. This paper reviewed and analyzed 607 papers related to urban green space and health behaviors from 2002 to 2021 in the Web of Science core collection by using Citespace 6.1.R2 software. The scientifically bibliometric analysis and visual analysis were conducted to analyze the basic characteristics, literature co-citation analysis, research hotspots, and frontier trends. The findings show that 11 co-citation clusters indicate the research intellectual base. Also, 19 main keywords with a high frequency and 20 main keywords with a high centrality were extracted. Burst detection analysis reveals three research frontier trends: the correlation between urban green space and health behavior; the driving and impact factors; and the study of environmental justice and social equity. This paper aims to systematically review the progress and basic situation of urban green spaces and health behaviors research around the world, which helps to have a comprehensive understanding of this field, as well as provide value and references for subsequent research.